2022
DOI: 10.1002/aenm.202200594
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Design Principles of Battery‐Supercapacitor Hybrid Devices: From Fundamental Mechanisms to Microstructure Engineering and Challenging Perspectives

Abstract: To this end, electrical energy storage (e.g., batteries, supercapacitors) has become a key supporting technology for the utilization of intermittent energy sources (e.g., sun, wind, nuclear energy). [3] Clearly, lithium-ion batteries (LIBs) are by far the most important electrochemical energy storage devices available for portable electronics, power tools, and electric vehicles on the market. However, LIBs suffer from the slow ion diffusion in electrode bulk, resulting in commercially achievable energy density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 281 publications
0
23
0
Order By: Relevance
“…Transparent energy storage devices have been drawing much attention in recent years due to the emergence of smart windows and the rapid development of solar cells and touchscreen electronics. Among all energy storage devices, supercapacitors show much promise due to their fast charging ability and cycling stability. Supercapacitors also bridge the gap between electrolytic capacitors and batteries in terms of energy and power densities. Various factors are evaluated for a transparent supercapacitor, including transparency, energy and power densities, specific capacitance, and cycle stability. ,, Among the materials for energy storage, poly­(3,4-ethylenedioxythiophene) (PEDOT) rises as one of the most promising supercapacitor electrode materials due to high conductivity, environmental stability, light weight, and ease of synthesis. , A major challenge for depositing this conducting polymer on a glass substrate is the lack of molecular interactions between organic and inorganic moieties resulting in poor adhesion and low cycle stability of the electrode. ,, Many studies overcome this challenge by embedding polymers in a framework, utilizing a sacrificial layer, or creating polymer/metal oxide composites. , However, these studies rely on glass with conductive coatings, such as fluorine-doped tin oxide or indium-doped tin oxide, that are both susceptible to dissolution in an acidic environment and potentially costly for large-scale implementation. Inspired by silanization and Friedel–Crafts alkylation mechanisms, ,− we present an alternative approach by covalently linking a polymer and glass through a self-assembled diphenyldimethoxysilane monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…Transparent energy storage devices have been drawing much attention in recent years due to the emergence of smart windows and the rapid development of solar cells and touchscreen electronics. Among all energy storage devices, supercapacitors show much promise due to their fast charging ability and cycling stability. Supercapacitors also bridge the gap between electrolytic capacitors and batteries in terms of energy and power densities. Various factors are evaluated for a transparent supercapacitor, including transparency, energy and power densities, specific capacitance, and cycle stability. ,, Among the materials for energy storage, poly­(3,4-ethylenedioxythiophene) (PEDOT) rises as one of the most promising supercapacitor electrode materials due to high conductivity, environmental stability, light weight, and ease of synthesis. , A major challenge for depositing this conducting polymer on a glass substrate is the lack of molecular interactions between organic and inorganic moieties resulting in poor adhesion and low cycle stability of the electrode. ,, Many studies overcome this challenge by embedding polymers in a framework, utilizing a sacrificial layer, or creating polymer/metal oxide composites. , However, these studies rely on glass with conductive coatings, such as fluorine-doped tin oxide or indium-doped tin oxide, that are both susceptible to dissolution in an acidic environment and potentially costly for large-scale implementation. Inspired by silanization and Friedel–Crafts alkylation mechanisms, ,− we present an alternative approach by covalently linking a polymer and glass through a self-assembled diphenyldimethoxysilane monolayer.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 The stringent performance and safety requirements of medium- and large-area energy storage formats have spurred a greater focus on the atomistic mechanisms and multiphysics coupling underpinning degradation phenomena. 3 , 4 , 5 , 6 In many cases, the origins of performance degradation are traceable to multi-field and multiphysics coupling originating at atomistic scales, manifested at mesoscale dimensions, and compounded up to the level of electrode architectures. 7 A detailed understanding of electrochemistry-mechanics coupling and resulting emergent phenomena across many decades of length scales is imperative to unlock unexploited performance from existing battery chemistries, develop dynamic process controls, and design next-generation materials and architectures that are purpose-built to alleviate common modes of degradation.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Moreover, even after rolling for the cathode, high pore volume would decrease the electronic conductivity and result in massive electrolytes filling in pores, leading to a significant decrease in energy density. 10 From the calculation of capacitance in eq 1, except for a high surface area (S), a small distance (d) between carbon walls and charged ions is a key parameter to increase the capacitance. In 2006, Gogotsi et al 11−13 found that if the pore size was close to the sizes of exposed ions (1 M TBABF 4 dissolved in PC), the ion desolvation will lead to an anomalous increase of capacitances.…”
Section: Introductionmentioning
confidence: 99%
“…as activators , for carbon precursors can gain a high surface area and is a straightforward solution for enhancing specific capacitance. However, the capacitance of porous carbon does not simply increase with the surface area in linear. , Moreover, even after rolling for the cathode, high pore volume would decrease the electronic conductivity and result in massive electrolytes filling in pores, leading to a significant decrease in energy density …”
Section: Introductionmentioning
confidence: 99%